Long-Term Palliative Effect of Stenting in Gastric Outlet Obstruction Due to Transarterial Chemoembolization with Yttrium-90 in a Patient with Metastatic Neuroendocrine Tumor - Erkan Caglar; Gulen Doğusoy; Levent Kabasakal; Ahmet Dobrucali (Korean Society of Gastrointestinal Endoscopy, 2016)
Internal radioembolization with yttrium-90 is a promising treatment method, predominantly for liver tumors. However, the shifting of yttrium-90-loaded spherules into the arteries and veins that supply the duodenum and stomach, leading to ulceration, hemorrhage, perforation, and outlet obstruction of these organs, is one of the major undesirable consequences of this technique. We report a case of gastric outlet obstruction (GOO) due to antropyloric stenosis with ulceration, edema, and inflammation following transarterial yttrium-90 treatment for a metastatic neuroendocrine tumor in a 58-year-old man. Stenting was used for palliation in this case. GOO improved after stenting and recovery of oral intake was permanent after stent removal.